The Cost-Effectiveness of Subsidies to Youth Employment in Italy: Toward a Preliminary Evaluation - Bruno Contini (Institute of Labor Economics (IZA), 2022)
The European Commission has for many years advocated fiscal policies in order to improve the employability of young people. This paper aims at providing a preliminary rough estimate of the cost-effectiveness of rebates on social security contributions granted to employers that Italy has utilized since the Nineties in a variety of forms. My conclusion is that cost-effectiveness is still an open question.
Keywords: J08; 330